PENERAPAN MODEL PEMBELAJARAN GERLACH DAN ELY DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V MATA PELAJARAN PAI DI SD NEGERI 020 LANGSAT HULU KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Nelawati Nelawati; Andrizal Andrizal; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2020)
Models, methods, strategies and approaches are important components in learning so students feel interested in following the lessons being taught. The Gerlach Dan Ely learning model is one of the cooperative learning models where the teacher can see the motivation, abilities and characteristics of students, so that it will be easier to convey the subject matter and make it easier to manage classrooms.As a subject are all 22 grade V students consisting of 12 men and 10 women and as an object is the application of the Gerlach and Ely learning model. Sentajo Raya, Kuantan Singingi Regency. With data collection techniques through observation, interviews, and documentation and data processing using percentage charts or bar charts.The application of the Gerlach Dan Ely learning model in class V students of PAI in 020 Langsat Hulu Elementary School, Sentajo Raya District, Kuantan Singingi District is good, namely pre-cycle rhymes are only 16.67, Cycle I 66.67%, and Cycle II rises to 100% . The application of the Gerlach and Ely learning modelcan increase student motivation in class V of PAI subjects at SD Negeri 020 Langsat Hulu Sentajo Raya District Kuantan Singingi. % and Cycle II increased to 85.45%.